Utilizing Areca catechu L. Fruit Peel-Derived Biochar and Hydrochar for Congo Red Adsorption: Kinetic and Thermodynamic Analysis - Adawiyah, Robiatul; Yuliasari, Nova; Hanifah, Yuliza; Alawiyah, Kamila; Rahayu Palapa, Neza (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2024)
This study explores the conversion of Areca fruit peel into carbon-based materials biochar (BC) and hydrochar (HC) for use as adsorbents in synthetic dye removal from wastewater. Conversion was achieved through pyrolysis for BC and hydrothermal carbonization (HTC) for HC. X-ray diffraction (XRD) analysis confirmed carbon formation, with both HC and BC showing an amorphous characteristics. FTIR analysis identified hydroxyl, carboxyl, acid, and ester functional groups in BC, HC and Areca fruit peel materials that are essential for adsorption. BET surface area measurements showed 82.584 m2/g for BC and 77.618 m2/g for HC. Adsorption experiments demonstrated CR removal capacities of 40.515 mg/g for HC and 40.616 mg/g for BC, significantly surpassing the 23.168 mg/g capacity of untreated Areca fruit peel. Over three regeneration cycles, both BC and HC retained structural integrity, highlighting their potential as reusable adsorbents for dye removal. These results suggest that Areca fruit peel-derived BC and HC are promising, sustainable adsorbents for wastewater treatment, particularly in mitigating environmental impacts from industrial dyes.